Capacidad antioxidante in vitro de las isoflavonas totales obtenidas de semillas de glycine max l. (soya) provenientes de la provincia de jaén-cajamarca”. - Díaz Solano, Hugo Ricardo (2010)
The amount of total isoflavones from seed of Glycine max L. (Soy) from the province of Jaén-Cajamarca, was determined using the method of Kostennikova Z., and in vitro antioxidant capacity of total isoflavones expressed as “antiradical efficiency” (A.E.) was determined using the method of Brand-Williams, et al; both methods adapted by the Department of Pharmacognosy and pharmacobotany of the Faculty of Pharmacy and Biochemistry of the UNT. The "antiradical efficiency” (A.E.) was calculated as the inverse of the product of the concentration of antioxidant needed to reduce by 50% the initial concentration of DPPH* "IC50"(obtained by linear correlation) and the time needed to achieve concentration IC50 “TIC50” (obtained by first order reaction kinetics) for total isoflavones that value was equal to 0.00250 x ng mL -1 x min-1. Both the IC50 as the TIC50 were determined graphically, both using the rates of capture of free radical 2,2-diphenyl-1-picrylhydrazyl (DPPH *).